Infrastructure Investment in World Bank Client Countries by Korean Sponsors - Jett, Alexander Nicholas (World Bank, Washington, DC, 2012)
From 1990-2010, project sponsors from the Republic of Korea implemented nineteen infrastructure projects in low and middle income countries with investment commitments totaling US$4.9 billion. Investment during all periods except 2001-2005 was dominated by the energy sector (US$4 billion), followed by the telecom sector (US$0.9 billion). Korean investment was spread across five regions; it was heavily concentrated in East Asia and the Pacific (EAP) region with 78 percent or total investment. This investment lacked a single country focus.